Efficacy of an Essential Oil-Based Pesticide for Controlling Bed Bug (Cimex lectularius) Infestations in Apartment Buildings - Wang, Changlu (Insects, 2014)
Bed bugs (Cimex lectularius L. and Cimex hemipterus F.) are among the most difficult urban pests to manage. Many essential oil-based bed bug control products that are considered reduced risk to mammals compared to synthetic insect neurotoxins have become commercially available, but their effectiveness as a stand-alone control method is unknown. This study assessed the field efficacy of an essential oil-based bed bug control product (EcoRaider; a.i. 1% geraniol + 1% cedar oil + 2% sodium lauryl sulfate) compared to a pyrethroid and neonicotinoid mixture spray (0.075% Temprid SC; a.i. beta-cyfluthrin + imidacloprid). After 12 weeks, the three treatments—EcoRaider, Temprid SC, and EcoRaider + Temprid SC caused 92.5 ± 2.7, 92.9 ± 3.0, and 91.7% ± 2.7% bed bug count reduction, respectively. No significant differences existed in the bed bug reduction among the treatments. Bed bugs were eliminated from only 22% of the treated apartments. Among those still with bed bugs, 76% of the residents did not know bed bugs were present. We documented the residents’ self-control practices and discussed the potential of using essential oil-based insecticides in bed bug management programs to minimize the health risks to building occupants and pets and to slow down the development of insecticide resistance.